Prevalence and molecular characterization of cystic echinococcosis in livestock in the Hazara Division, Pakistan - Arbab, Safia; Ullah, Hanif; Hassan, Inam Ul; Suleman; Wang, Weiwei; Qadeer, Abdul; Zhang, Jiya (Frontiers in Veterinary Science, 2025)
IntroductionEchinococcosis is a parasitic zoonotic disease caused by Echinococcus tapeworm larvae, forming cysts in organs like the liver and lungs. It primarily affects livestock and humans, with significant public health and economic implications worldwide. In the Hazara Division, the prevalence and genetic diversity of the Echinococcus is largely unexplored. Therefore, the current study aims to assess the prevalence of Echinococcus granulosis (EG) in livestock.Materials and methodsFrom April 2023 to April 2024, a total of 480 livestock animals, including buffaloes, cattle, goats, and sheep, were examined for echinococcosis across various slaughterhouses in the Hazara Division. Cysts of Echinococcus were collected from different organs, and the cyst fluid (CF) was microscopically analyzed before DNA extraction. PCR amplification was performed targeting the Cox1 (317 bp) and Cyto B (309 bp) genes to confirm the presence of E. granulosus.ResultsThe overall prevalence of Cystic echinococcosis (CE) was 12.2% (59/480), with rates observed in different species as follows: cattle (13.1%), buffaloes (15.2%), goats (6.3%), and sheep (5.7%), (p-0.658). District-wise, higher prevalence rates were recorded in Haripur and Mansehra districts (17.5% and 16.2%), followed by Abbottabad and Battagram (12.5% and 11.2%). The lowest prevalence of infection was observed in the upper and lower Kohistan districts, with rates ranging from (8.7% and 7.5%), respectively. The infection was more common in male animals than in females, particularly among those older than 4-5 years (p =0.048). Sex-wise prevalence varied across species, with cattle showing rates of 12.4% in males and 14.3% in females. In buffaloes, prevalence was 20% in males and 13.3% in females, followed by sheep at 5% in males and 6.2% in females, and goats at 8% in males. Most animals in the study were older than three years, with the highest number of cysts found in animals over five years of age. Hydatid cysts were most found in the liver (39.1%) and lungs (34.7%), followed by the kidneys (17.3%) and heart (8.6%), (p-0.01).ConclusionIn conclusion, E.G. is highly prevalent in the livestock population of the Hazara division.